2007
DOI: 10.3892/or.18.3.601
|View full text |Cite
|
Sign up to set email alerts
|

The overexpression of caveolin-1 and caveolin-2 correlates with a poor prognosis and tumor progression in esophageal squamous cell carcinoma

Abstract: Abstract. Caveolin-1 (CAV1) and caveolin-2 (CAV2) are the major structural proteins of caveolae. We investigated the relationship between the clinicopathological factors of esophageal squamous cell carcinoma (ESCC) and the expression of CAV1 and CAV2. CAV1 and CAV2 expression were analyzed by quantitative reverse transcription-polymerase chain reaction (RT-PCR) in 15 esophageal cancer cell lines (TE1-15) and a normal esophageal epithelium cell line (Het-1A). CAV1 and CAV2 expression was examined by RT-PCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 24 publications
4
76
1
Order By: Relevance
“…We recently reported that Cav-1 expression level is correlated positively with clinical TNM stage and histologic grade of tongue SCC (23). Other studies have reported that overexpression of Cav-1 in esophageal SCC is correlated with T factor, lymphatic invasion, vein invasion, differentiation and overall survival of patients (24). Based on the results of the esophageal carcinomas and our present results, it suggested that Cav-1 expressed in the same histologic type of carcinoma from different organs might have similar function.…”
Section: ------------------------------------------------------------mentioning
confidence: 98%
“…We recently reported that Cav-1 expression level is correlated positively with clinical TNM stage and histologic grade of tongue SCC (23). Other studies have reported that overexpression of Cav-1 in esophageal SCC is correlated with T factor, lymphatic invasion, vein invasion, differentiation and overall survival of patients (24). Based on the results of the esophageal carcinomas and our present results, it suggested that Cav-1 expressed in the same histologic type of carcinoma from different organs might have similar function.…”
Section: ------------------------------------------------------------mentioning
confidence: 98%
“…Likewise, Caveolin-1 expression is increased in multi-drug resistant MCF7 breast cancer cells [47] and promotes anchorage-independent survival by preventing anoikis [48][49]. In patients, Caveolin-1 presence is associated with elevated metastasis, multi-drug resistance and poorer prognosis [50][51][52]. Interestingly, Caveolin-1 is associated with polarized distribution of cell signaling components and Caveolin-1 is required for cell polarization and migration in two and three dimensions [53][54][55].…”
Section: Caveolin-1 In Multi-drug Resistance and Metastasismentioning
confidence: 99%
“…Caveolin-1 was first thought to have tumour suppressor properties (Razani et al, 2001a, b;Hnasko and Lisanti, 2003), based on the finding of an arguable inactivating point mutation in CAV1, the silencing of CAV1 gene expression by promoter hypermethylation in breast cell lines and prostate tumour samples (Engelman et al, 1999;Hurlstone et al, 1999;Cui et al, 2001) and the apparent downregulation of CAV1 in breast cancer (Chen et al, 2004;Park et al, 2005). In recent years, there has been increasingly more coherent data to suggest that CAV1 and CAV2 may also have oncogenic properties in breast (Hurlstone et al, 1999;Pinilla et al, 2006; Van den Eynden et al, 2006;Savage et al, 2007Savage et al, , 2008, prostate (Yang et al, 1998;Thompson et al, 1999), bladder (Rajjayabun et al, 2001;Fong et al, 2003), oesophageal (Kato et al, 2002;Ando et al, 2007), thyroid, pancreatic, non-small cell and squamous lung cancer (Kato et al, 2004;Sunaga et al, 2004).…”
mentioning
confidence: 99%